(untitled) (Journal of Hama University, 2024)
Dry eye is one of the common complications after corneal refractive surgery: Laser in Situ Keratomileusis (LASIK) and Photorefractive Keratoctomy (PRK). In this study, we evaluated dry eye signs and symptoms following PRK and LASIK with the goal of identifying which develops dry eye. It is a retrospective study case conducted on 80 patients who underwent LASIK or PRK with myopia for two years. Results: The average age of patients was 25,3±1,5 years (range 19-39). We measured the tear film break–up time, Schirmer test I, OSDI index, rose Bengal staining. Conclusion: We observed higher levels of dry eye after LASIK compared to PRK after two years.